189k views
5 votes
To solve this system of equations by elimination, what operation could be used to eliminate the y-variable and find the value of x? 2x − 4y = 6 −3x + 3y = 12

User Jholloman
by
4.4k points

2 Answers

3 votes
2x - 4y = 6
-3x + 3y = 12

In order to find x (first) you need to eliminate y

3( 2x - 4y = 6)
4( -3x + 3y = 12)

6x -12y = 18
-12x +12y = 48

y cancels out and you should now have

6x - 12x = 18 +48
Simplify the equation;

-6x = 66
Divide both sides by - 6 to get x by itself,

x = 11
User Gloria
by
5.7k points
4 votes

Answer:

x = -11

Explanation:

The given system of the equations is

2x - 4y = 6 -------(1)

-3x + 3y = 12 --------(2)

To eliminate the variable y, multiply equation 1 by 3 and multiply equation 2 by 4 and add them

3(2x - 4y) + 4(-3x + 3y) = 6×3 + 12×4

6x - 12y - 12x + 12y = 18 + 48

-6x = 66

x = -
(66)/(6)

x = -11

Therefore, value of x is (-11).

User Yue Wang
by
5.1k points